Proceedings of the Twenty-Fifth ACM SIGMOD-SIGACT-SIGART Symposium on Principles of Database Systems 2006
DOI: 10.1145/1142351.1142377
|View full text |Cite
|
Sign up to set email alerts
|

Finding and approximating top-k answers in keyword proximity search

Abstract: Various approaches for keyword proximity search have been implemented in relational databases, XML and the Web. Yet, in all of them, an answer is a Q-fragment, namely, a subtree T of the given data graph G, such that T contains all the keywords of the query Q and has no proper subtree with this property. The rank of an answer is inversely proportional to its weight. Three problems are of interest: finding an optimal (i.e., top-ranked) answer, computing the top-k answers and enumerating all the answers in ranke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 26 publications
1
149
0
Order By: Relevance
“…In addition, in the previous work [27], the graph represents actual data items and their associations, and the Steiner trees are possible answers containing given keywords. Since data graphs can be very large, the method is primarily of theoretical rather than practical interest.…”
Section: K-best Steiner Treesmentioning
confidence: 99%
“…In addition, in the previous work [27], the graph represents actual data items and their associations, and the Steiner trees are possible answers containing given keywords. Since data graphs can be very large, the method is primarily of theoretical rather than practical interest.…”
Section: K-best Steiner Treesmentioning
confidence: 99%
“…In addition, in [6] it is shown that the optimal q-fragments of r can be enumerated in ranked-order with polynomial delay, i.e., the time for printing the next optimal answer is again polynomial in the size of r. Hence, we can state the following preliminary result. Theorem 1.…”
Section: Algorithm 3: Pruning (Prune(t Q))mentioning
confidence: 90%
“…An efficient method for solving this problem in the context of keyword search over structured data is presented in [6], where a q-fragment can model our notion of answer. Yet, when optimality is not required, a simple technique (quadratic in the size of r) to obtain an answer (steps 2-6 of Algorithm 3) consists in trying to remove any tuple from the set as long as it contains all the keywords and remains connected.…”
Section: Keyword-based Answering In the Deep Webmentioning
confidence: 99%
“…We first compute s 1,l for each l (lines 2-5), then compute s k,l as discussed. Meanwhile, we record array best, which is used to re-produce the optimal DFS, newDF S (lines [11][12][13][14][15][16][17]. Finally, DoD is calculated by comparing newDF S with every other DFS (lines 18-21).…”
Section: Figure 4: Recurrence Relationmentioning
confidence: 99%
“…Many approaches have been proposed for supporting keyword search on XML data [4,8,9,14,15,16,17,19,22,24,18], and keyword search on graphs / relational databases [10,23,1,2,12,20,6,16,13,7]. Various ranking schemes have been proposed in these studies, including IR-style ranking (term frequency, document frequency, etc.…”
Section: Related Workmentioning
confidence: 99%